FUNGSI RITUAL TARI TOTOK’NG PADI DI DESA SABA’U KECAMATAN SAMALANTAN KABUPATEN BENGKAYANG KALIMANTAN BARAT - Riny Martha; Imma Fretisari; Ismunandar Ismunandar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe Function of the Totok’ng Padi Dance Ritual in Saba’u Village, Samalantan District, Bengkayang Regency, West Kalimantan. Essay. Pontianak: Performing Arts Education Study Program, Departemen of Language and Arts Education, Faculty of teacher Training and Education, Tanjungpura University. The author of this thesis analyzes the ritual function of Totok’ng Padi Dance in Saba’u village, Samalantan District, bengkayang Regency. The title of this tesis was raised to find out the function of the of full blooded rice until it became a performing art. The purpose of this research is Totok’ng Padi Dance is influential or not in art, ritual Functions and becomes a performing art in Saba’u village, Samalantan Distrct. This research uses quantitative method, this research is carried of with preli minary research plans, colleting primary and secondary data, analizing data and making research reports ( thesis )the research location is in Saba’u village, Samalantan District, Bengkayang Regency. The researchsample is thepeople of Saba’u Village. The conclusion in this study is that the ritual Function of the Totok’ng Padi Dance was originally a ritual, over time the ritual dance becamea performance Dance and is often displayed every year at the naik Dango Even at the Samalantan Traditional House.Keywords : Ritual function, Perfroming Arts